2019
DOI: 10.32598/jhnm.29.4.210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Home Care on Husband’s Support During the Postpartum Period

Abstract: The role of Fathers' involvement and support in the care of mother and child during postpartum is crucial. This support promotes the health of the mother and the family. Objective: This study aimed to determine the effect of home care on the husband's support during the postpartum period. Materials and Methods: This is a clinical trial conducted on 64 women given birth in one of the hospitals in Isfahan, Iran. They were randomly assigned into two groups of intervention and control. A researcher-made questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Studies have indicated that postnatal training can be effective in mothers' successful breastfeeding. Baghersad et al (2020) conducted a study to investigate the effect of postpartum care at home on mothers' health. The mothers in the intervention group received 2 sessions postpartum care program.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that postnatal training can be effective in mothers' successful breastfeeding. Baghersad et al (2020) conducted a study to investigate the effect of postpartum care at home on mothers' health. The mothers in the intervention group received 2 sessions postpartum care program.…”
Section: Discussionmentioning
confidence: 99%
“…Tool critical appraisal dalam scoping review menggunakan The Joanna Briggs Institute (JBI). The Joanna Briggs Institute ini untuk menilai kualitas metodologis studi dan untuk menentukan sejauh mana sebuah studi membahas kemungkinan bias dalam desain, perilaku dan analisis 4 Dari beberapa artikel ditemukan data berupa karakteristik nama Negara,dan tahun penelitian :…”
Section: Penilaian Kritis (Langkah 4)unclassified
“…After the labor process at a health facility, the mother continues postpartum care at home. This home care program is also expected to increase husband's support towards a safe postpartum period (Baghersad, Mokhtari & Bahadoran, 2019).…”
Section: Informational Supportmentioning
confidence: 99%